Portulaca oleracea leave extract enhanced renal function via enhancing urea and creatinine clearance in wistar rats - Naiho Alexander Obidike; Emojevwe Victor; Oyovwi Mega Obukohwo; Ohwin Peggy Ejiro; Osamah Ngozi Blessing (European Journal of Medicinal Chemistry Reports, 2024)
Portulaca oleracea is rich in several minerals, vitamins, and antioxidant components, which has made it widely used in the management of hepato-renal disorders. In this study, we aimed to establish the safety or otherwise effect of Portulaca oleracea on renal function in albino Wistar rats concerning its numerous uses in traditional medicine as a vegetable for humans and as animal feed. The rats were grouped into experimental and control groups of ten (10) rats each. The experimental group was fed with 200 mg/kg of portulaca oleracea extract incorporated into the diet, while the control group was fed with normal feed for 4 weeks. Blood samples were collected for analysis. The data obtained was analyzed using a student t-test. The result of the test showed that creatinine from the experimental group (0.28 ± 0.03 mg/dL, p = 0.002) showed a significant decrease when compared with the control group (0.37 ± 0.02 mg/dL) at p<0.05. Urea from the experimental group (28.57 ± 2.77 mg/dL, p = 0.002) showed a significant decrease as compared to the control group (37.175 ± 2.27 mg/dL). Sodium (174.66 ± 5.38 mEq/L, p = 0.007), potassium (13.07 ± 0.48 mEq/L, p = 0.016) and calcium (9.94 ± 1.05 mEq/L, p = 0.043) of portulaca group showed significant increase when compared with their respective control values (143.19 ± 4.70; 9.22 ± 3.10; 8.52 ± 0.83mEq/L) at p<0.05. It could therefore be concluded that Portulaca oleracea extract at a dose level of 200 mg/kg has a beneficial effect on renal function by enhancing creatinine and Urea clearance and improving serum sodium, potassium and calcium concentration.